Hubungan Iklim Sekolah dengan Motivasi Berprestasi Tenaga Administrasi Sekolah di SLTP Kecamatan Ranah Pesisir - Nadya Hanifah Rahma; Anisah Anisah; Nellitawati Nellitawati; Lusi Susanti (CV. ITTC INDONESIA, 2026)
School administrative staff are one of the components of educational personnel who play an important role in supporting the smooth implementation of education through various administrative and school service activities. This study aimed to determine the level of achievement motivation among school administrative staff, assess the condition of the school climate, and determine whether there was a significant relationship between school climate and the achievement motivation of school administrative staff in junior high schools in Ranah Pesisir District. This study employed a quantitative approach using a correlational method. The research population consisted of 42 school administrative staff, and the sample consisted of 42 respondents selected using simple random sampling with the Slovin formula at a 5% margin of error. Data were collected using a Likert-scale questionnaire consisting of 25 items for the school climate variable and 25 items for the achievement motivation variable. Data were analyzed using descriptive statistics, normality tests, linearity tests, Pearson correlation, and t-tests with the assistance of SPSS version 26. The results showed that the achievement motivation of school administrative staff was categorized as high, with a mean score of 4.24 and an achievement level of 85.7%. The school climate was categorized as good, with a mean score of 4.46 and an achievement level of 89.3%. However, the correlation test showed a correlation coefficient of 0.014 with a significance level of 0.929. The t-test resulted in a t-count of 0.090, while the t-table value was 2.021 at df = 40 and a significance level of 0.05. Since the t-count was lower than the t-table value and the significance level was greater than 0.05, the alternative hypothesis was rejected. Therefore, there was no significant relationship between school climate and the achievement motivation of school administrative staff in this study.